2016
DOI: 10.1111/mec.13769
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of resistance to virus infection in Drosophila

Abstract: Variation in susceptibility to infection has a substantial genetic component in natural populations, and it has been argued that selection by pathogens may result in it having a simpler genetic architecture than many other quantitative traits. This is important as models of host–pathogen co‐evolution typically assume resistance is controlled by a small number of genes. Using the Drosophila melanogaster multiparent advanced intercross, we investigated the genetic architecture of resistance to two naturally occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 59 publications
3
65
0
Order By: Relevance
“…On the other hand, more broad antiviral mechanisms also exist, such as those involving non-specific RNA degradation (Table 1). In Drosophila populations, mutant flies can be identified that are resistant to viruses that naturally infect Drosophila but not to viruses with broad host range usually not encountered in nature [208]. Analysis of the mutants reveals antiviral defense mechanisms that are different from RNAi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, more broad antiviral mechanisms also exist, such as those involving non-specific RNA degradation (Table 1). In Drosophila populations, mutant flies can be identified that are resistant to viruses that naturally infect Drosophila but not to viruses with broad host range usually not encountered in nature [208]. Analysis of the mutants reveals antiviral defense mechanisms that are different from RNAi.…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide association studies have revealed polymorphisms that have major effects on resistance against viruses that naturally infect Drosophila, but not against other viruses [91,92]. Through long-term evolution with natural infections, viral resistance can emerge either by changing the immune system (at the level of "antiviral genes") or by altering host factors that are used by the virus during its replication cycle (at the level of "proviral genes") [93].…”
Section: Mutations In Drosophila Populations That Confer Resistance Amentioning
confidence: 99%
“…For example, the increased use of isogenic lines propelled by the DGRP-Drosophila melanogaster Genetic Reference Panel , has inaugurated an era of unprecedented studies in Drosophila GWAS studies (Huang et al, 2012;Jordan et al, 2012;Magwire et al, 2012;Weber et al, 2012;Kislukhin et al, 2013;Swarup et al, 2013). In parallel, the development of recombinant inbred lines that constitute the Drosophila Synthetic Population Resource (DSPR) have provided another important resource for the dissection of the genetic basis of complex traits (King et al, 2012;Burke et al, 2014;Marriage et al, 2014;Cogni et al, 2016). Before this, isofemale lines had been at the core of fecund research programs aiming at describing and comparing genomic variation between D. melanogaster and its sister species (Begun et al, 2007), and comprehending their genotype-phenotype map (Hoffmann et al, 1990;Turelli and Hoffmann, 1995;Lazzaro et al, 2004Lazzaro et al, , 2006Scott et al, 2011;Zhu et al, 2012;Ventura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Molecular Ecology, Cogni et al (2016) add significantly to the understanding of the genetic basis of resistance to viruses in Drosophila. The authors use the Drosophila Synthetic Population Resource (DSPR) panel (http://wfitch.bio.uci.edu/~dspr/; Long et al 2014) to identify the genes involved in Drosophila differential survival to DCV and sigma virus (Fig.…”
mentioning
confidence: 99%
“…This issue has been gaining momentum in recent years with the accelerated development of novel genetic and genomic techniques and resources. In this issue of Molecular Ecology, Cogni et al (2016) address the genetic basis of resistance to two viruses in Drosophila melanogaster using a panel of recombinant inbred lines with unprecedented resolution allowing detection of rare alleles and/or alleles of small effect. The study confirms the role of previously identified genes of major effect and adds novel regions with minor effect to the genetic basis of Drosophila resistance to the Drosophila C virus or the sigma virus.…”
mentioning
confidence: 99%